2014
DOI: 10.1002/anie.201409815
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Alkylation of Acylsilanes

Abstract: The highly enantioselective addition of Grignard reagents to acylsilanes is catalyzed by copper diphosphine complexes. This transformation affords α-silylated tertiary alcohols in up to 97% yield and 98:2 enantiomeric ratio. The competing Meerwein-Ponndorf-Verley reduction is suppressed by the use of a mixture of Lewis acid additives. The chiral catalyst can be recovered as a copper complex and used repeatedly without any loss of catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 49 publications
0
45
0
11
Order By: Relevance
“…[2] Consequently,c atalytic asymmetric methods for their preparation are in demand, and several approaches are available,s uch as additions to either acylsilanes with hydrides [3] or aldehydes with silicon nucleophiles [4] and hydrogenation of a-silyl enol carbamates. [8][9][10] The groups of Marek [8] and Chan [9] reported zinc-promoted alkynylations of acylsilanes with terminal alkynes as pronucleophiles (Scheme 1, top). [8][9][10] The groups of Marek [8] and Chan [9] reported zinc-promoted alkynylations of acylsilanes with terminal alkynes as pronucleophiles (Scheme 1, top).…”
mentioning
confidence: 99%
“…[2] Consequently,c atalytic asymmetric methods for their preparation are in demand, and several approaches are available,s uch as additions to either acylsilanes with hydrides [3] or aldehydes with silicon nucleophiles [4] and hydrogenation of a-silyl enol carbamates. [8][9][10] The groups of Marek [8] and Chan [9] reported zinc-promoted alkynylations of acylsilanes with terminal alkynes as pronucleophiles (Scheme 1, top). [8][9][10] The groups of Marek [8] and Chan [9] reported zinc-promoted alkynylations of acylsilanes with terminal alkynes as pronucleophiles (Scheme 1, top).…”
mentioning
confidence: 99%
“…To avoid the reduction pathway and at the same time activate the imine towards the addition of Grignard reagents, the optimization studies for the catalytic reaction were carried out in the presence of super-stoichiometric amounts of a mixture of BF 3 ·OEt 2 and CeCl 3 . This Lewis acid assisted synthesis was developed during our previous studies, where we found that a mixture of BF 3 ·OEt 2 and CeCl 3 prevents the undesired reduction pathway in the synthesis of tertiary alcohols16 and that BF 3 ·OEt 2 can activate inherently unreactive substrates such as alkenyl-heteroarenes towards nucleophilic addition of Grignard reagents14.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, if used in the alkylation of ketimines, their high reactivity might be helpful to overcome the low reactivity of the latter. Despite these obvious advantages, and the plethora of methods employing Grignard reagents for catalytic asymmetric C–C bond formation with Michael acceptors121314, aldehydes15 and ketones1617 not a single catalytic asymmetric reaction involving the direct addition of Grignard reagents to ketimines has been reported. Thus, a general protocol for the catalytic enantioselective addition of Grignard reagents to ketimines would be an important step forward in the synthesis of α-chiral amines with tetrasubstituted carbon stereocentre.…”
mentioning
confidence: 99%
“…[5] Diese Reaktionsvorschriften bieten einen Zugang zu enantiomerenangereicherten sekundären a-Silylalkoholen, aber die Reduktionen kçnnen nicht auf tertiäre Systeme übertragen werden. [8][9][10] Die Gruppen von Marek [8] und Chan [9] berichteten über zinkvermittelte Alkinylierungen von Acylsilanen mit terminalen Alkinen als Pronukleophile (Schema 1, oben). [8][9][10] Die Gruppen von Marek [8] und Chan [9] berichteten über zinkvermittelte Alkinylierungen von Acylsilanen mit terminalen Alkinen als Pronukleophile (Schema 1, oben).…”
unclassified
“…[12][13][14][15][16][17][18][19] Damit werden dicht funktionalisierte Borverbindungen mit hoher Regio-und Stereokontrolle zugänglich gemacht. [10] Wiru ntersuchten als nächstes die Anwendungsbreite an Acylsilanen (Schema 2). [14a, 15b,16c-e,18c,d, 19a] isoliertem Produkt und Enantiomerenüberschüsse wurden auf der Stufe des 1,3-Diols 4 nach oxidativem Abbau der C-B-Bindung in 3 bestimmt.…”
unclassified